Evaluating the effectiveness of the geriatrician-designed “Older Patient Care and Seek Course” for family physicians - Esra Ates Bulut; Zeynep Kemik; Feride Gozen; Ali Ekrem Aydın; Ersin Akpinar; Derya Kaya; Ahmet Turan Isık (Frontiers in Medicine, 2026)
Background The population is aging and many primary care providers report gaps in managing complex geriatric conditions. This study aims to evaluate the effectiveness of a six-hour training program delivered by geriatricians in improving family physicians' knowledge and understanding of geriatric syndromes. Methods The study included 22 participants who attended an “Older Patient Care and Seek Course” held during an international family physicians congress. The course consisted of six hours of in-person, interactive presentations on the major geriatric syndromes. Prior to the training, participants completed an 18-item pre-test assessing their knowledge in areas such as preventive care, polypharmacy, pressure injuries, malnutrition, and cognitive impairment. Following the training, the same test was administered as a post-test to evaluate changes in knowledge. Each item was scored as one point. Results Of the participants, 86.4% were women, with a median age of 30 years (range: 27–40). Additionally, 54.5% were family medicine specialists, and the remainder were family medicine residents. The median duration of post-graduate clinical experience was 5 years (range: 2–17). In terms of test results, the mean pre-test score was 9.00 ± 1.74, which significantly increased to 14.59 ± 1.89 on the post-test. The difference between pre- and post-test scores was statistically significant ( p < 0.01). Conclusions Education plays a critical role in recognizing and effectively addressing the needs of the geriatric population within primary healthcare settings. Implementing structured, interactive, comprehensive postgraduate CME programs led by geriatricians is an effective strategy to promote awareness and improve identification of geriatric syndromes among primary care specialists.